2020
DOI: 10.1016/j.jped.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Patients with asthma have reduced functional capacity and sedentary behavior

Abstract: Children and adolescents undergoing regular asthma treatment showed reduced functional capacity and sedentary behavior. The lower the quadriceps strength, the shorter the distance walked; the higher the tumor necrosis factor-α levels, the lower their daily physical activity levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…They also were the ones who reported a more sedentary lifestyle, including increased screen time, decreased physical activity, and decreased sleep duration. The associations between obesity, nutritional changes, sedentary lifestyle and the development of asthmatic symptoms as well as poor asthma control are well known, 33,34 and such changes in lifestyle during COVID-19 are emerging. 35 Our study also showed worrisome numbers of caregivers with heightened anxiety and increased concern for their child's health.…”
Section: Discussionmentioning
confidence: 99%
“…They also were the ones who reported a more sedentary lifestyle, including increased screen time, decreased physical activity, and decreased sleep duration. The associations between obesity, nutritional changes, sedentary lifestyle and the development of asthmatic symptoms as well as poor asthma control are well known, 33,34 and such changes in lifestyle during COVID-19 are emerging. 35 Our study also showed worrisome numbers of caregivers with heightened anxiety and increased concern for their child's health.…”
Section: Discussionmentioning
confidence: 99%
“…Villa et al 33 reported a reduction in muscle resistance in the quadriceps of asthmatic children. On the other hand, Reimberg et al 40 did not observe differences in muscle strength between asthmatic and healthy children. 33 Among several factors that may contribute to alter muscle strength, sedentary time is considered as an important one and our results demonstrated a decrease in the levels of daily physical activity in children with asthma when compared to their healthy peers.…”
Section: Discussionmentioning
confidence: 88%
“…Another significant factor was the increment in sedentary lifestyle. Caregivers reported further augmentation of sedentary habits during the third lockdown compared to the first one, which could be correlated to the well-known association of poor asthma control and sedentary lifestyle [ 33 , 34 ]. This is especially relevant to patients older than 5 years of age, who were more likely to worsen clinically during the third lockdown and in line with global results of the worrisome effects of increased sedentary behaviors during COVID-19 lockdowns [ 35 , 36 ], supporting the propensity for clinical worsening and increased sedentary lifestyle observed by us earlier [ 14 ].…”
Section: Discussionmentioning
confidence: 99%